PENGENALAN TEKNOLOGI MOBIL LISTRIK PADA SISWA SMA NEGERI 2 KOTABARU - Andie; Hasanuddin; Hendra Sanjaya (JURNAL ABDIMAS DOSMA (JAD), 2026)
Electric vehicles (EVs) are environmentally friendly vehicles powered by an electric motor and battery, serving to reduce greenhouse gas emissions. However, public understanding of the technology, advantages, and disadvantages of electric cars is still limited. A Community Service activity was conducted at SMA Negeri 2 Kotabaru, where students faced challenges in assembling an electric car, specifically with its battery, electrical systems, and software. Furthermore, myths among the teachers created apprehension about using electric vehicles. This outreach program aimed to introduce EV technology, educate on its pros and cons, and increase public awareness and acceptance. The methods used included lectures, discussions, and demonstrations. The expected outcome of this activity is an increase in public knowledge and acceptance of electric cars as an eco-friendly technology. Therefore, broader and more intensive outreach is necessary to promote the general use of environmentally friendly technologies.